A quantum inspired evolutionary algorithm for dynamic multicast routing with network coding - Xing, Huanlai; Xu, Lexi; Qu, Rong; Qu, Zhijian (2016)
This paper studies and models the multicast routing problem with network coding in dynamic network environment, where computational and bandwidth resources are to be jointly optimized. A quantum inspired evolutionary algorithm (QEA) is developed to address the problem above, where a restart scheme is devised for well adapting QEA for tracing the ever-changing optima in dynamic environment. Experimental results show that the proposed QEA outperforms a number of existing evolutionary algorithms in terms of the best solution obtained.